2015
DOI: 10.1556/crc.2014.0050
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield enhancement through fungicide application on maize hybrids with different susceptibility to northern corn leaf blight

Abstract: Foliar fungicides are widely used to control pests on several crops and, from mid-2000s, have become more common on maize. The yield advantages derived from foliar fungicides on maize, as for other crops, could be related not only to the direct control of the disease, but also to physiological effects on the plant. The aim of the research was to evaluate the response of maize to the application of an azoxystrobin and propiconazole mixture. The fungicide was applied to hybrids with different susceptibility to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Unlike the biomass yield at dough stage, the fungicide application, acting on IPAR in a longer maturation period, could have led to grain yield advantages. In fact, the yield enhancement of +5%, obtained by means of the fungicide sprayings during the tassel emergence stage, has confirmed the data reported in previ-ous experiments, in which similar compounds were tested on maize sown at a standard planting density (Munkvold et al, 2001;Paul et al, 2011;Testa et al, 2015). It has been reported that both active ingredients play roles in stimulating photosynthesis (Gooding et al, 2000;Petit et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Unlike the biomass yield at dough stage, the fungicide application, acting on IPAR in a longer maturation period, could have led to grain yield advantages. In fact, the yield enhancement of +5%, obtained by means of the fungicide sprayings during the tassel emergence stage, has confirmed the data reported in previ-ous experiments, in which similar compounds were tested on maize sown at a standard planting density (Munkvold et al, 2001;Paul et al, 2011;Testa et al, 2015). It has been reported that both active ingredients play roles in stimulating photosynthesis (Gooding et al, 2000;Petit et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…QoI-containing fungicides have in general been shown to provide greater physiological benefits and to increase grain yield through enhanced plant performance, even during the absence of disease in maize (Nelson and Meinhardt, 2011) or in other crops (Bertelsen et al, 2001;Kato et al, 2011). The fungicide physiological enhancement effect allows a better translocation of the metabolic resources (starch) from the source organs (leaves) to the sink (ear), as it prevents their allocation from actively defending the plant against the pathogen (Petit et al, 2012;Testa et al, 2015). Conversely, the addition of epoxiconazole AI to the QoI fungicide has confirmed, as other DMI fungicides, to have a greater ability of restraining NCLB development (Bowen and Pedersen, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current control strategies for NCLB encompass resistance breeding, chemical treatments, and biological control [38,39]. Chemically spraying fungicides during the corn tasseling period remains a prevalent preventive measure against NCLB, with propiconazole, azoxystrobin, and pyraclostrobin being common choices [40,41]. In this study, toxicity assessments revealed that fludioxonil exhibited the highest toxicity, followed by C-14 demethylation inhibitors, including tebuconazole, hexaconazole, and propiconazole.…”
Section: Discussionmentioning
confidence: 83%
“…A direct crop enhancement effect of fungicide seed dressing may be related to the physiological effect that certain fungicide compounds could exert on plants, even in the absence of a fungal infection. Strobilurins have been shown to induce physiological benefits for different crops, such as longer-lasting green leaf tissue and delayed plant senescence (stay green effect), through a reduction in oxidative stress [36], an increase in photosynthesis efficiency, for higher true photosynthesis, and a reduction in dark respiration [37]. Enhanced maize performance, even in the absence of disease, has also been reported for foliar applications of azoxystrobin [38] and pyraclostrobin [39] from the stem elongation stage to flowering.…”
Section: Discussionmentioning
confidence: 99%